Construtos narrativos: um mosaico de historicidade do fazer pedagógico no Centro Federal de Educação Tecnológica do Amazonas - CEFET-AM (2001 a 2008) - Rodrigues, Maria da Conceição Oliveira (2023)
The present research is constituted by the central objective of investigating the Pedagogical Doing in the Federal Center of Technological Education of Amazonas (CEFET-AM), between the years 2001 and 2008, from the realities of the institutional policies. This theme emerged from the perspective of understanding the process of institutional implantation in the context of the reorganization of Professional and Technological Education, mainly in Manaus (locus of the research), being the headquarters unit of CEFET-AM. The theme was not a random conception, but represents the possibility of studying the experiences, constructions of representations of time-space meanings narrated by subjects who participated and acted in technical-pedagogical functions in the phases of existence of CEFET-AM. Among the research theorists, with a phenomenological approach, we highlight Bicudo (2020), who brings in this context the understanding of the phenomenon of investigation of the experiences of social subjects and how they give meaning to the world around them, Clandinin and Connelly (2015), in support of narrative research developed to understand the experiences of social subjects, Koselleck (2006) which constitutes the understanding of the space of experience, contexts and historical concepts, Le Goff (1990) in the investigation of the relationship between time, memory and history, in addition to Moraes and Galiazzi (2020) in the theoretical methodological contribution of Discursive Textual Analysis, as a data analysis tool. The study had a descriptive character with a qualitative approach based on the process of narratives produced by the 5 (five) social subjects (in the research, called crystals), and we used as data collection instruments: field information from the first approximations visit to the Moacir Andrade Museum, the Professor Paulo Sarmento Library, the General Coordination of People Management (CGGP/CMC/IFAM), Documentary Research, application of a questionnaire and narrative interview. Among other aspects, we point out as results obtained, recording the feeling of receptiveness of society at the time, in the projection of improvements and institutional and educational advances with CEFET-AM, mainly by offering higher education courses, expanding the higher education network with investments in teaching, research, extension and revitalization of courses aimed at professional and Technological Education. On the other hand, we perceive, with the data of the subjects' speeches, criticisms related to the discontinuity of the pedagogical sector, disarticulation in the implantation of the new system of education and the recognition of the national policy directed toward the educational formation aiming to attend the labor of the industrial sectors. From the study, we elaborated the Educational Product using the audiovisual documentary genre, under the title of “The Pedagogical Narrative Mosaic: Memories and Trajectories of CEFET-AM (2001 to 2008)”. For this, we used the metaphor of crystals to represent the research subjects and the tesserae, fillets and fragments of the mosaic as the research findings. In the production of the presented resource, we emphasize that this type of genre allows the application as a didactic tool, of composition in theoretical contexts in the scopes of school and academic contexts and represents a way of revitalizing the memories and stories of the social actors in the (re) construction of the Do Pedagogical of the time.